WTAP mediates IL-1β-induced chondrocyte injury by enhancing CA12 mRNA stability depending on m6A modification - Gang Deng; Yizhou Xu; Zhengnan Li; Guangxuan Zeng (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoarthritis (OA) poses a significant risk to the mobility of patients. Carbonic anhydrase 12 (CA12) can boost apoptosis and inflammation in several cancers, but its role in OA is unknown. Methods Differentially expressed genes in OA were analyzed using the GEO database (GSE169077). RT-qPCR and western blot estimated relative mRNA and protein levels of CA12. Cell viability and apoptosis were estimated by cell counting and flow cytometry assays. Oxidative stress (OxS) was determined by detecting with ROS and MDA levels, as well as CAT and SOD activities. Cytokine levels of IL-6 and TNF-α were detected by ELISA. Parameters associated with apoptosis and extracellular matrix (ECM) were detected by western blot. The m6A modification profile was determined by methylated RNA immunoprecipitation assays. Results Relative CA12 and wilms’ tumor 1-associating protein (WTAP) mRNA and protein levels were overexpressed in OA articular cartilages and IL-1β-challenged chondrocytes CHON-001. CA12 silencing impaired IL-1β-induced cell apoptosis, inflammation, OxS, and ECM degradation in chondrocytes. Yet, CA12 overexpression exerted an opposing function. WTAP reinforced the stability of CA12 mRNA depending on the m6A modification. Furthermore, WTAP knockdown weakened cell apoptosis, inflammation, OxS, and ECM degradation in chondrocytes induced by IL-1β, but these changes were impaired after CA12 overexpression. In addition, WTAP knockdown mitigates cartilage degeneration in DMM-induced mouse models. Conclusion IL-1β-induced WTAP enhances CA12 mRNA stability depending on m6A modification, thus promoting chondrocyte apoptosis, inflammatory response, OxS, and ECM degradation, providing evidence to support the possibility of WTAP and CA12 as potential targets for OA treatment.